2006
DOI: 10.1021/om0608051
|View full text |Cite
|
Sign up to set email alerts
|

Dimethyl Group IV Metal Complexes of the OSO-Type Ligand Bearing AlMe2Moieties

Abstract: Complexes haVing two ancillary (tbop) 2ligands where tbopH 2 ) 2, 2′-thiobis{4-(1,1,3,3-tetramethylbutyl) Viz.,S,O) 2 ] (M ) Ti, 1; M ) Zr, 2; M ) Hf, 3), haVe been prepared in good yields by amine or HCl elimination from tbopH 2 . The 1 H and 13 C NMR studies showed that complexes 1-3 adopt in solution mononuclear structures. Treatment of 1-3 with 2 equiV or an excess of AlMe 3 generates heterometallic [M(µ-tbop-κ 3 O,S,O) 2 Me 2 (µ-AlMe 2 ) 2 ] (M ) Ti, 4; M ) Zr, 5; M ) Hf, 6) complexes. The structures of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…In the post-metallocene era, there is a continuing interest in the development of new transition metal-based catalysts for α-olefin polymerization, which is fueled by the search for new ligand frameworks that improve the understanding of structure−property relationships. Rational ligand design based upon this knowledge leads to better control over polymerization parameters such as activity, selectivity, livingness, and comonomer incorporation ability and may open access to polymeric materials otherwise unavailable. ,, An emerging class of non-metallocene catalysts are group 4 metal complexes based on aryloxide ligands functionalized with heteroatom donors. These ligands allow tuning of the electronic and steric properties of the resulting precatalysts. , …”
Section: Introductionmentioning
confidence: 99%
“…In the post-metallocene era, there is a continuing interest in the development of new transition metal-based catalysts for α-olefin polymerization, which is fueled by the search for new ligand frameworks that improve the understanding of structure−property relationships. Rational ligand design based upon this knowledge leads to better control over polymerization parameters such as activity, selectivity, livingness, and comonomer incorporation ability and may open access to polymeric materials otherwise unavailable. ,, An emerging class of non-metallocene catalysts are group 4 metal complexes based on aryloxide ligands functionalized with heteroatom donors. These ligands allow tuning of the electronic and steric properties of the resulting precatalysts. , …”
Section: Introductionmentioning
confidence: 99%
“…In a pioneering work, Kakugo and co-workers synthesized titanium complexes derived from [OSO]-type bis(phenol)s, and showed that, when activated with methylaluminoxane (MAO), these complexes could act as versatile pre-catalysts in the polymerization of ethylene and α-olefins, and the copolymerization of ethylene with styrene [ 17 , 18 ]. Janas et al reported the preparation of [OSO]-type titanium complexes possessing a long sterically hindered auxiliary group such as 1,1,3,3-tetramethylbutyl group ortho to the phenoxide moiety [ 19 , 20 , 21 , 22 ]. These complexes, supported on MgCl 2 , showed extremely high activity for the ethylene polymerization (204,760 g mmol −1 h −1 ) upon activation with AlEt 2 Cl.…”
Section: Introductionmentioning
confidence: 99%
“…Although simple group 4 metal bis-phenoxide catalysts are active, additional neutral donors are often incorporated into the ligand frame to occupy sites of coordinative unsaturation not needed for chain growth ,, Such additional donors may also help to “rigidify” the structure of the complex and open up the possibility for stereoselective polymerizations using prochiral olefins.…”
Section: Introductionmentioning
confidence: 99%
“…However, there is growing evidence that softer second-row donors may offer beneficial stabilization of the highly reactive metal center While there have been a growing number of reports concerning catalysts that combine phenoxides with thioether donors a,b, e, c,h, g, , there has been little focus on ligands containing tertiary phosphines c,d,j, , Therefore bis( o -phosphanylphenoxide) complexes of the group 4 metals , appeared attractive; additional benefits include (i) a fairly straightforward synthesis ( vide infra ) with several sites around the ligand amenable to elaboration, (ii) a rigid phenylene bridge, which should help to enforce phosphine coordination, and (iii) an active species that could parallel the highly active group 4 metal phenoxyimine systems and offer a new class of early transition metal polymerization catalyst with the potential to influence polymer microstructure and stereochemistry.…”
Section: Introductionmentioning
confidence: 99%